Influence of tool rotational speed on the properties of friction stir spot welded AA7075-T6/Al2O3 composite joint. (2020) - Suresh, S.; Venkatesan, K.; Natarajan, Elango; Rajesh, S.
Abstract: The growing importance of Aluminium alloys in automobiles and aerospace applications provides the implementation of composite materials and promising joining method like Friction Stir Spot Welding (FSSW). In this research, Al2 O3 nanoparticles reinforced FSSW is carried out on 7075-T6 Aluminium alloy and the influence of tool rotational speed on mechanical properties is studied. The base metal of thickness of 2 mm is spot welded using a threaded cylindrical profile tool with four different tool rotational speeds varying between 900 rpm and 1700 rpm, where volume of Al2 O3 is being unchanged. The results of mechanical tests show that the sample made with a tool rotational speed of 1300 rpm has a better weld of good strength. Moreover, the result from Field Emission Scanning Electron Microscopy also evidences the uniform distribution of Al2 O3 nanoparticles in the weld region which causes the improved strength. Also observed that the lower and higher tool rotational speeds from the selected range do not result homogeneous distribution of nano fillers in the weld nugget.